(untitled) (Annals of Medical Research, 2023)
Aim: It was aimed to compare the clinical and radiological results of total hip arthroplasty performed with the anterolateral approach with the literature. Materials and Methods: 65 patients who underwent total hip arthroplasty with anterolateral approach between 2016-2021 were included. Preoperative and postoperative functional status evaluations of the patients were performed using the Harris hip score. In the clinical evaluation of the patients, thigh pain, wound infection, length of hospital stay, body mass index, duration of surgery and complications were also evaluated. In the radiological evaluation, the acetabular and femoral relaxation zones, the presence and amount of vertical and horizontal migration of the acetabular component, the presence and amount of femoral vertical migration, the position of the femoral component, the femoral dorr classification, the angle of inclination of the acetabular component and the presence of heterotrophic ossification were examined. Results: Of the patients, 29 (44.6%) were male and 36 (55.4%) were female. The mean age of the patients was 61.65 and the mean follow-up period was 40.2 months. Considering the diagnoses of the patients, THA was applied to 51 (70.8%) patients for coxarthrosis, 14 (19.4%) for avascular necrosis, 5 (6.9%) patients for fractures, and 2 (2.8%) patients for septic arthritis. The mean preoperative Harris Hip Score of the patients was 34.2 (18.1-59.9). The mean postoperative Harris Hip score was 88.5 (68.8-96). When the postoperative Harris Hip Score of the patients was evaluated, 53 (73.6%) were evaluated as excellent results, 18 (25%) as perfect results, and 1 (1.4%) as good results. Conclusion: In our study, the results of total hip arthroplasty performed with the anterolateral approach were successful and satisfactory surgery when performed with appropriate indications and planning.